Needs Analysis on English Professional Skills for Students of Islamic Banking Department - Citra Liza; Andriadi Andriadi (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to identify professional English language skill requirements for students in Islamic Banking program and to propose an optimal English learning concept tailored for students at UIN Fatmawati Sukarno Bengkulu. The goal is to adequately address the professional needs of students in their future work environments. Employing a qualitative approach, the study involved interviews with Islamic Banking students, Islamic Banking lecturers, stakeholders from the Islamic Banking authority in Bengkulu Province, and English lecturers. The findings indicate that English proficiency is crucial for Islamic Banking students, as their future professions involved using English banking terminology and meeting requirements for advancement to managerial positions. Communication targets in the professional realm encompass correspondence, banking applications, leadership meetings, interactions with large companies, managerial-level managers, and handling foreign customers. English language situations in banking affairs predominantly occur at the managerial level, involving transaction handling in large and foreign companies, report preparation, and central-level reporting processes. A learning situation analysis reveals that proficiency in all English language skills is imperative in the profession within Islamic financial institutions. Considering the workplace needs in Islamic banking institutions, the ideal English learning concept involves mastering language elements and skills, coupled with activities supporting productive professional communication through authentic audio-visual teaching materials. Learning activities span from listening and learning Islamic banking vocabulary to practicing their use in dialogues and delivering presentations in English. Employing communicative learning methods, peer learning, and role play is essential to motivate students to regularly practice English and become accustomed to it, as well as the use of constructivism learning models.